The Roles of Potassium Channels and Nitric oxide in the Modulation of Apelin induced-relaxation in Isolated Diabetic Rat Aorta - Othman, Hawzheen K.; Mahmud, Almas MR.; Maulood, Ismail M. (Iraqi Journal of Science, 2024)
Diabetes is associated with endothelial dysfunction, which impairs blood vesselscapacity to maintain vascular tone. Apelin is an adipocyte-produced relaxing factor that has endothelium-dependent and nitric oxide (NO)-mediated vasorelaxant effects. The current study investigated how streptozotocin (STZ)-induced type one diabetes modulates the mechanisms involved in aortic vascular response to apelin, focusing on the role of potassium channels and endothelial derived relaxing factors (EDRF). In this study, precontracted rat thoracic aortic segments were pre-incubated with the NO inhibitor, cyclooxygenase (COX) inhibitor and potassium channels blockers including: non-selective calcium-activated potassium channel, big conductance calcium-activated potassium channels (BKca), intermediate conductance calcium activated potassium channels (IKca), delayed inward rectifier potassium channels (Kir), adenosine triphosphates-sensitive potassium channels (KATP) and voltage sensitive potassium channels (Kv) blockers, then cumulative concentrations of apelin were applied to each group in both non-diabetic and diabetic conditions. The statistical analysis between diabetic and non-diabetic groups revealed that endothelial impairment induced by diabetes in rat thoracic aorta remarkably attenuated the vascular responses to apelin. An important new finding in this study was that almost all potassium channels blockers noticeably P<0.001 increased apelin efficacy with relatively no changes in the peptide potency. However, in diabetic aortic segments, the non-selective Kca, BKca blockers, NO inhibitor and COX inhibitor reversed vascular responses to apelin, but Kir, KATP and Kv blockers significantly reduced vascular responses to apelin in comparison to control rats. It is worth noting that diabetes did not only alter the peptide potency in these experimental groups but also significantly increased the maximum responses when Kca and BKca blockers preincubated. In conclusion, our findings shed light on the mechanisms behind diabetes-induced aortic artery hypo-reactivity to apelin which involve the inhibition of endothelial NO synthase activities and decreased contribution of Kca, BKca, IKca, Kv, Kir and KATP channels.